Remaining strength of Girth welded pipelines due to corrosion defects - Tan, Douglas Tsong Kai (2015)
Corrosion is an electrochemical process that causes a loss of material in offshore pipelines where the remaining strengths reduce as corrosion advances. Numerous studies have been performed to determine the failure pressures of corroded pipelines, but corrosion on pipelines with additional girth weldings still leave much to be understood. This project used ABAQUS (version 6.10) to perform Finite Element Methods to compare against various studies and offshore manuals. 90 girth welded pipelines with various corroded depths and lengths were simulated and the results showed that they deviated from current studies and manuals. An equation was developed to predict the failure pressures of corroded girth welded pipelines.